2014
DOI: 10.1001/jamapediatrics.2013.5483
|View full text |Cite
|
Sign up to set email alerts
|

Parental Monitoring of Children’s Media Consumption

Abstract: Importance Although children's media consumption has been one of the most robust risk factors for childhood obesity, effects of specific parenting influences, such as parental media monitoring, have not been effectively investigated. Objectives This study examined the potential influences of maternal and paternal monitoring of child media exposure and children's general activities on children's BMI in middle childhood. Design A longitudinal study, taken from a subsample of the Three Generational Study, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Interestingly parental monitoring of children’s eating was correlated with low scores for screen time problematic behavior. A recent US study has reported how maternal monitoring of preschoolers’ media time was associated with lower child BMI SDS [ 45 ]. Together the results suggest that monitoring is an important parenting practice for promoting a healthy lifestyle for children [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly parental monitoring of children’s eating was correlated with low scores for screen time problematic behavior. A recent US study has reported how maternal monitoring of preschoolers’ media time was associated with lower child BMI SDS [ 45 ]. Together the results suggest that monitoring is an important parenting practice for promoting a healthy lifestyle for children [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described in Tiberio et al (2014) weight and height of the G3 child were measured using scale and tape when assessments occurred on site, and in other cases from parents by phone. To correct for age variation in the assessments the z BMI then was calculated relative to national norms (i.e., not a z -score based on the present sample mean).…”
Section: Methodsmentioning
confidence: 99%
“…Parents also can help children manage bullying or offset its negative effects (e.g., Bowes, Maughan, Caspi, Moffitt, & Arseneault, 2010). Additionally, parent behaviors and characteristics influence the child risk characteristics that are linked with victimizing peers and being victimized, such as aggression, social withdrawal, poor social skills, and obesity (e.g., Albuquerque, Stice, Rodríguez-López, Manco, & Nóbrega, 2015; Kim, Capaldi, Pears, Kerr, & Owen, 2009; Shaffer, Burt, Obradović, Herbers, & Masten, 2009; Tiberio et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A better conceptualization of restriction and control is needed to understand the positive and negative effects on weight development [ 37 , 45 , 53 , 54 ]. Parental monitoring has also been associated with healthy child behaviors and weight status, but the strength of associations is not as strong [ 49 , 55 57 ], possibly due to parents awareness of the importance of such practices (social desirability) leading to high floor and ceiling effects in responses to items [ 58 ].…”
Section: Introductionmentioning
confidence: 99%